Identidade nacional, memória coletiva e sua relação com a participação política em estudantes de universidade pública, Perú, 2018 - Laurente, Itala (2022)
Objective: To determine the relationship between national identity, collective memory, and political participation among university students. Method: This study employed an applied research approach with a quantitative orientation, utilizing a correlational design and a non-experimental methodology. A probabilistic sample was selected using a simple random technique, and data was collected through the use of a questionnaire. Results: The combined variable of national identity and collective memory was found to have no significant correlation with political participation. There was a low correlation between collective memory and political participation, while a negative correlation was observed between national identity and political participation. Conclusions: The findings indicate that students develop a sense of national identity during their school, family, or university years. They exhibit a positive attitude towards the future of the economy and recognize the existence of corrupt individuals in Peru. However, the social and educational conditions do not support personal and national development. Regarding collective memory, there is some knowledge about political violence. In terms of political participation, students demonstrate limited involvement in party politics, consider the existence of labor unions important, and perceive student movements differently. There is a need to strengthen the concept of leadership among students. Additionally, there is partial participation in volunteering activities, but limited involvement in organizations and events promoting peace or human rights.